1994
DOI: 10.1161/01.str.25.5.974
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygen extraction, oxygen consumption, and regional cerebral blood flow during the aura phase of migraine.

Abstract: Background and PurposeThe aura phase of migraine is associated with focal blood flow changes, but it has been largely unknown whether these changes are correlated to changes in the cerebral metabolism.Methods Eight patients required carotid angiography for evaluation of transient neurological attacks. Cerebral blood flow (CBF) results, angiography, and clinical observations subsequently suggested the diagnosis: migraine with aura and occasional aura attacks without headache. In the same setting the cerebral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 18 publications
3
51
0
Order By: Relevance
“…Our data confirmed previous reports that CSD-like phenomena can be seen with neuroimaging techniques (7,10,12,15,19,20,28). Like those previous studies, our data indicated a slowly spreading area of abnormal blood flow in the occipital lobe during migraine aura.…”
Section: Discussionsupporting
confidence: 92%
“…Our data confirmed previous reports that CSD-like phenomena can be seen with neuroimaging techniques (7,10,12,15,19,20,28). Like those previous studies, our data indicated a slowly spreading area of abnormal blood flow in the occipital lobe during migraine aura.…”
Section: Discussionsupporting
confidence: 92%
“…3 Patients who undergo imaging examination during an aura characteristically have hypoperfusion, whereas those who undergo imaging examination during the headache phase characteristically show hyperperfusion. 4,29,30 The findings in this case series provide support for the vascular theory of migraine headaches. However, the more popular migraine theories suggest a contiguously spreading wave of cortical neuronal depression.…”
Section: 28supporting
confidence: 70%
“…Vascular features are part of the headache family and this has made it natural to use rCBF methods in the search for pathophysiological mechanisms (Friberg et al 1994;Hachinski et al 1977;Olesen et al 1990). In migraine there is to date no consensus of the signi¢cance regarding the changes in CBF that have been demonstrated, i.e.…”
Section: (A) Headache and Migrainementioning
confidence: 99%